Revisiting COVID-19 vaccine hesitancy around the world using data from 23 countries in 2021 - Jeffrey V. Lazarus; Katarzyna Wyka; Trenton M. White; Camila A. Picchio; Kenneth Rabin; Scott C. Ratzan; Jeanna Parsons Leigh; Jia Hu; Ayman El-Mohandes (Nature Communications, 2022)
Vaccine hesitancy is a public health challenge. Here the authors examine COVID-19 vaccine hesitancy in June 2021 using a survey including individuals from 23 countries, and report differences compared to a year earlier.